Avaliação do jambolão (Syzygium cumini) sobre os biomarcadores cardiovasculares e a morfologia dos tecidos hepático e adiposo em camundongos submetidos a uma dieta hiperlipídica - Bernardes, Roberta de Oliveira (2017)
The cardiovascular diseases (CVD) are the main cause of mortality all over the world. The consumption of food, rich in antioxidants, as the phenolic compounds presented in jambolan (Syzygium cumini), may be an alternative to reduce the risk of CVD development. The objective of this work was to evaluate the action of lyophilized jambolan upon cardiovascular biomarkers fed a high-fat diet. The jambolan was lyophilized and its centesimal composition, total phenolic content, and total anthocyanins and the in vitro antioxidant capacity were determined. For the biological assay 43 mice were demanded and they were submitted to a normal-fat control diet (CT, n=22) and high-fat diet (HF, n=22), during 8 weeks. Thereafter, for a new period of 9 weeks, the CT group was divided and continued to receive CT diet (n=10) or CT diet supplemented with 2% of lyophilized jambolan (CT+J, n=12); the group HF continued receiving HF diet (n=9) or HF diet supplemented with 2% of lyophilized jambolan (HF+J, n=12). Thus, the animals were submitted to euthanasia and blood samples were collected for the analysis of metabolic and inflammatory biomarkers. The liver histological analysis and epididymal adipose tissue analysis were carried out. The results were analyzed by t test to evaluate the CT and HF groups, before the supplementation period. The “Two-way” variance analysis was carried out to evaluate the effect of the diet and fruit and/or their interactions among the experimental groups (CT, HF, CT+J and HF+J). The data were expressed in arithmetic mean and standard errors, with 5% significance level. The experimental model was efficient on checking higher weight gain on the animals, which received high-fat diet. The high-fat diet potentized the inflammatory process, promoting an increase on the total cholesterol concentrations, increase on the epididymal fat, promotion of hepatic steatosis and expression of inflammatory biomarkers as ICAM-1 and ALT. The diet supplementation with 2% of lyophilized jambolan was efficient on reducing some damages present on the inflammatory process and/or related to the cardiovascular risk, decreasing the concentrations of e-selectin. It was also possible to observe the effect of jambolan on the reduction of ICAM-1 concentrations, when in association with high-fat diet. The fruit also presented hepatoprotective effect, with reduction on the AST concentrations and protection of the liver against lipid infiltration and consequent hepatic steatosis.